PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE PERFORMANCE TERHADAP EFISIENSI OPERASIONAL PERBANKAN YANG DIMODERASI OLEH ADOPSI INOVASI E-BANKING - Putri, Amalia; Apandi, Nelly Nur; Prawira, Ida Farida Adi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine and explain the influence of environmental, social, and governance (ESG) perfomance and the adoption of e-banking innovations on banking operational efficiency, as well as how the interaction with the adoption of e-banking innovations moderates this relationship in banking companies listed on the Indonesia Stock Exchange for the period 2021-2024. The population in this study consists of banks listed on the Indonesia Stock Exchange, with a total population of 47 banks. The sampling method used in this study employs purposive sampling, resulting in 13 banks listed on the Indonesia Stock Exchange during the 2021-2024 period as the sample for the study. The research method used is a descriptive approach with a quantitative methodology. Multiple linear regression analysis and moderation regression analysis were used to test the effect of environmental, social, and governance (ESG) performance and e-banking innovation adoption on banking operational efficiency and its interaction with e-banking innovation adoption. The results of the study indicate that environmental, social, and governance (ESG) performance and the adoption of e-banking innovations influence banking operational efficiency. Furthermore, the interaction of e-banking adoption does not moderate the relationship between the influence of environmental, social, and governance (ESG) performance on banking operational efficiency